The role of educational games in promoting students’ visit at Sony Sugema Library - Wulandari, Yayu; Ilmiah, Amina Bina; Tresnawan, Hanifa Akmalia; Putrisolichat, Shafa Nurul Azmi (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. Sony Sugema Library managed by SD Alfa Centauri faces the challenge of low student interest in visiting. To overcome this, the library increases students' interest in reading by providing facilities such as educational and creative games as the main solution. In addition, the library provides relevant readings, literacy programs such as read aloud, student reading awards, and competitions on national days. This study aims to explain the board game strategy to attract students to the library and increase their involvement in literacy activities Data Collection Methods. The method used in this research is field research Data Analysis. Involving direct observation and interaction at Sony Sugema Library, with data collected through observation, interviews, and documentation studies Results and Discussion. The results showed the importance of attracting students' interest in visiting the library and using promotional strategies such as children's games like the Seblak Quartet card game, Scrabble, Jenga, memory games, Guess Me, 5 Second Rule, and 5 Pillars. Conclusion. The strategy of providing educational and creative games can be an effective solution for increasing interest in visiting the library and participation in literacy activities. This effort is supported by other literacy programs to strengthen student engagement in reading culture